Uncovering the neural control of laryngeal activity and subglottic pressure in anaesthetized rats: insights from mesencephalic regions. - González-García, Marta; Carrillo-Franco, Laura; Morales-Luque, Carmen; Ponce-Velasco, Marina; Gago-Calderón, Belén; Dawid-Milner, Marc Stefan; López-González, Manuel Víctor (Springer, 2024)
To assess the possible interactions between the dorsolateral Periaqueductal Gray matter (dlPAG) and the laryngeal motor neurons of the nucleus Ambiguus (nA), we have examined the pattern of double staining c-Fos/FoxP2 protein immunoreactivity (c-Fos-ir/Fox-P2-ir) and Tyrosine Hydroxylase (TH) throughout the rostro-caudal extent of nA in spontaneously breathing anaesthetised male Sprague–Dawley rats during dlPAG electrical stimulation. Activation of the dlPAG elicited a selective increase in c-Fos-ir with an ipsilateral predominance in the somatas of the loose (p<0.05) and compact formation (p<0.01) within the nA and confirm the expression of FoxP2 bilaterally in all the domains within the nA. A second group of experiments was made to examine the importance of the dlPAG in modulating the laryngeal response evoked after electrical or chemical (glutamate) dlPAG stimulations. Both electrical and chemical stmulations evoked a significant decrease of laryngeal resistance (subglottal pressure) (p<0.001) accompanied with an increase in respiratory rate together with a pressor and tachycardic response. The results of our study contribute with new data on the role of the mesencephalic neuronal circuits in the control mechanisms of subglottic pressure and laryngeal activity.
Keywords: Laringe; Neuronas motoras; Dorsolateral periaqueductal gray matter; Subglottic pressure; Nucleus ambiguous; Laryngeal motoneurons; Central cardiorespiratory control; Rat